Occupation-based activity analysis - Thomas, Heather 1971- (SLACK Incorporated, 2015)
Occupational therapists use occupations and activities as not just a goal, but also as a treatment medium, therefore, they must understand both the uniqueness of a client's occupations and how an activity can be used therapeutically. To analyze the complexity of an occupation takes much more depth of understanding of the person engaging in it, his or her environment, and the uniqueness of the occupation a person has chosen. The new Second Edition of Occupation-Based Activity Analysis continues the tradition of teaching students and clinicians the process of conducting activity analyses and occupation-based activity analyses. Dr. Heather Thomas has updated Occupation-Based Activity Analysis, Second Edition to reflect the significant changes made to the activity analysis process and terminology in the Occupational Therapy Practice Framework, Third Edition. As in an activity analysis, occupation-based activity analysis looks at what is required for full participation, yet goes beyond analyzing the activity; it looks at what it means for the person engaging in it and how and where it is performed by that person. Inside Occupation-Based Activity Analysis, Second Edition, each chapter is dedicated to a component of the activity analysis process and corresponding section of the Framework. Chapters have been restructured based on a greater emphasis on occupation-based activity analysis. From start to finish, readers are guided through identifying the occupation, sequence and timing, objects and properties, space and social demands, body functions, and structures and performance skills required"--